Current issues and best practices of secretarial profession - Ikulor, Felicia Seledi (Journal of Professional Secretaries and Office Administrators, 2013)
Current issues and best practices in secretarial profession was researched and seen the importance of technological advancement in the global trend. This result proves that the usage of automated office equipment diversified the secretarial profession to secretarial technology, in enhancing the secretary for effective usage of the equipment and service delivery. Changing remain paramount, the old conventional method of carrying out secretarial functions is changing to modern technological way which promotes efficiency in the service delivery as a current issue in all modernized offices. This paper points the values and importance of a secretary who have the technological idea to meet-up the demand of servicing in the global trend. The paper evaluates the function of the secretary to how the innovative fact be mastered and to carry out a proper function through computer and IT training. Finally, recommendations are made for way out and also to acquire the technological skills which to enable the secretarial professionals to function in all organizational firms and more effective delivery of services in all level of governance.